New ways to learn geography – challenges of the 21st century - Markuszewska, Iwona; Tanskanen, Minna; Subirós, Josep Vila (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2018)
The aim of the article is to get a closer overview of the non-instructional methods of the teaching-learning process of geography. To achieve this goal, the results of the international project Borderland: Border Landscapes Across Europe (undertaken in 2012 and 2013, within the framework of LLP-Erasmus Programme) was presented. Special attention was paid on the innovative approach to learning methods, namely learning by doing (LBD) that was experienced in a multinational environment during the project’s implementation.
Keywords: geography; landscape; borderland; cross-border learning; learning by doing (LBD)